(untitled) (Iranian Journal of Kidney Diseases, 2013)
Primary ciliary dyskinesia is characterized by congenital impairment of mucociliary clearance. Kartagener syndrome (KS) is a clinical variant of primary ciliary dyskinesia which is involved in situs inversus associated with chronic respiratory infections. In addition, glomerular disease in KS syndrome is rare and reported cases are limited. We had a 27-year-old female patient with KS who presented with proteinuria, hematuria, normal kidney function, and a family history of systemic lupus erythematosus. Kidney biopsy showed segmental scar with adhesion to Bowman capsule, which was indicative of focal segmental glomerulosclerosis.